A Comparative Study of the Microbiological Efficacy of Polymyxin B on Different Carbapenem-Resistant Gram-Negative Bacteria Infections - Lu, Qiong; Zhu, Hai-Hong; Li, Guo-Hua; Qi, Ting-Ting; Ye, Liang-Jun; Teng, Xin-Qi; Qu, Qiang; He, Ge-Fei; Qu, Jian (Frontiers in Medicine, 2021)
Objective: The emergence of carbapenem-resistant gram-negative bacteria (CR-GNB) has brought great challenges to clinical anti-infection treatment around the world. Polymyxins are often considered as the last line of defense in the treatment of CR-GNB infections. In this study, we explored the microbiological efficacy of Polymyxin B (PMB) on different CR-GNB infections as well as the factors influencing microbiological efficacy. Methods: CR-GNB infected patients with PMB-based regimens were enrolled. Clinical and microbiological data were collected from the medical electronic record system of the Second Xiangya hospital. The efficacy of PMB on different CR-GNB was evaluated by the clearance rate at 7-days and within the course of treatment, as well as the 30-day mortality rate. Results: A total of 294 CR-GNB infected patients were enrolled:154 CR-Acinetobacter baumannii (CRAB), 55 CR-Klebsiella pneumoniae (CRKP), and 85 CR-Pseudomonas aeruginosa (CRPA). The CRAB group had the highest 7-day bacterial clearance rate [(CRAB: 39.0%) vs. (CRKP: 29.4%) vs. (CRPA: 14.5%), P=0.003] and total bacterial clearance rate [(CRAB: 49.0%) vs. (CRKP: 39.8%) vs. (CRPA: 18.2%), P<0.001] among the three groups, while the bacterial clearance rate of the CRPA group was the lowest. Multivariate logistic regression showed that the differences among the three groups were multiple CR-GNB infections (P=0.004), respiratory infections (P=0.001), PMB resistance (P<0.001), and the combination of tigecycline (P<0.001). Binary logistic regression showed that multiple CR-GNB infection [(7-day bacterial clearance: P=0.004) & (total bacterial clearance: P=0.011)] and bacterial species [(7-day bacterial clearance: P<0.001) &(total bacterial clearance: P<0.001)] were independent risk factors for microbiological efficacy. Conclusion: PMB exhibited differential microbiological efficacy on different types of CR-GNB infections; it had the best effect on CRAB, followed by CRKP and CRPA. Multiple CR-GNB infections and bacterial species were independent risk factors for microbiological efficacy.